Mergers and industry concentration in Britain - A. HUNTER (PSL Quarterly Review, 2014)
The principal concern of policy on mergers regards their alleged propensity to increase the concentration of industry thus reducing the intensity of competition or even creating some substantial degree of monopoly. Apart from the dangers arising from concentration and large size, however, mergers can provide many economic benefits and secure an essential element in the flexibility and economic growth of industry. The present article analyses mergers and industry concentration in Britain. The experience of past merger waves is first reviewed. The author then analyses the objectives, motivations and conditions for mergers. Finally, mergers policy in Britain is considered.